Dread nation [rise up.] - Ireland, Justina (Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
"Jane McKeene was born two days before the dead began to walk the battlefields of Gettysburg, Pennsylvania...derailing the War Between the States and changing the nation forever. In this new America, safety for all depends on the work of a few, and laws like the Native and Negro Education Act require certain children attend combat schools to learn to put down the dead. But there are also opportunities...and Jane is studying to become an Attendant, trained in both weaponry and etiquette to protect the well-to-do. It's a chance for a better life for Negro girls like Jane. After all, not even being the daughter of a wealthy white Southern woman could save her from society's expectations. But that's not a life Jane wants. Almost finished with her education at Miss Preston's School of Combat in Baltimore, Jane is set on returning to her Kentucky home and doesn't pay much mind to the politics of the eastern cities, with their talk of returning America to the glory of its days before the dead rose. But when families around Baltimore County begin to go missing, Jane is caught in the middle of a conspiracy, one that finds her in a desperate fight for her life against some powerful enemies. And the restless dead, it would seem, are the least of her problems."...
Subtitle from dust jacket. - Includes bibliographical references
Keywords: Horror fiction / gsafd; Horror fiction / lcgft; Historical fiction / lcgft; Novels / lcgft; YOUNG ADULT FICTION / Action & Adventure / Survival Stories / bisacsh; YOUNG ADULT FICTION / Historical / United States / Civil War Period (1850-1877) / bisacsh; YOUNG ADULT FICTION / People & Places / United States / African American / bisacsh; Conspiracies -- Juvenile fiction; Zombies -- Juvenile fiction; African Americans -- Juvenile fiction; Horror tales; Young adult fiction; Conspiracies; Zombies; African Americans; Horror stories; YOUNG ADULT FICTION / Action & Adventure / Survival Stories; YOUNG ADULT FICTION / Historical / United States / Civil War Period (1850-1877); YOUNG ADULT FICTION / People & Places / United States / African American; Baltimore (Md.) -- Juvenile fiction; Baltimore (Md.); Jugendbuch